2007
DOI: 10.1063/1.2766696
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar organic field-effect transistors based on a low band gap semiconductor with balanced hole and electron mobilities

Abstract: The authors have demonstrated the thin-film properties and the ambipolar transport of a delocalized singlet biradical hydrocarbon with two phenalenyl radical moieties (Ph2-IDPL). The organic field-effect transistors (OFETs) based on Ph2-IDPL exhibit ambipolar transport with balanced hole and electron mobilities in the order of 10−3cm2∕Vs. The Ph2-IDPL film is an organic semiconductor with a low band gap of 0.8eV and has small injection barriers from gold electrodes to both the highest occupied molecular orbita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
98
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 24 publications
4
98
0
2
Order By: Relevance
“…100 In addition, Chikamatsu et al demonstrated thin-film properties of 8d and ambipolar transport with balanced electrons and holes, presumably due to its amphoteric redox properties and strong intermolecular electronic communications. 101 It is worth noting that only low hole and electron mobilities up to 10 À3 cm 2 (V s) À1 were observed despite strong intermolecular coupling of this molecule, which was a result of the amorphous structure and poor crystallinity of the film. But still, those results indicate a bright future for stable biradical PAHs in materials science.…”
Section: Bis(phenalenyl) Biradicalsmentioning
confidence: 98%
“…100 In addition, Chikamatsu et al demonstrated thin-film properties of 8d and ambipolar transport with balanced electrons and holes, presumably due to its amphoteric redox properties and strong intermolecular electronic communications. 101 It is worth noting that only low hole and electron mobilities up to 10 À3 cm 2 (V s) À1 were observed despite strong intermolecular coupling of this molecule, which was a result of the amorphous structure and poor crystallinity of the film. But still, those results indicate a bright future for stable biradical PAHs in materials science.…”
Section: Bis(phenalenyl) Biradicalsmentioning
confidence: 98%
“…[8,[17][18][19][20][21] Ambipolar transistors have been reported from the active channels of multilayers, [2,22,23] blends or bulk heterojunctions of unipolar organic semiconductors, [3,[11][12][13]17] single active materials with asymmetric metal electrodes of different workfunctions, [20] and single-component materials with a common electrode. [3][4][5][6][7][8][9][10]19,[24][25][26][27][28] Charge-carrier mobilities in the range of 10 À5 to 0.1 cm 2 V À1 s À1 have been reported in the case of ambipolar OFETs based on solution-processable, singlecomponent semiconductors. [3][4][5][6][7][8][9]19,27,28] Such ambipolar transistors have been integrated into inverters, which results in output voltage gains of $6-18.…”
mentioning
confidence: 99%
“…[1][2][3][4] It is commonly believed that organic semiconductors are generally both hole and electron conductors, [5] and that their mostly unipolar behavior is caused by interface trapping of electrons or by a too high charge injection barrier resulting from a drastic mismatch of the highest occupied and lowest unoccupied molecular orbital (HOMO and LUMO) energy levels with the workfunction of the source and drain electrodes. [6] This latter hurdle in realizing ambipolar transistors can be overcome by the introduction of two different electrodes, each facilitating either electron or hole injection.…”
mentioning
confidence: 99%